Cutaneous Angiosarcoma in an Unusual Location and Without Predisposing Factors - Oliveira Monteiro, Ana (Eur J Case Rep Intern Med, 2020)
Cutaneous angiosarcoma is a rare, highly malignant tumour of vascular endothelial origin. It usually arises in the skin and superficial soft tissue, mostly on the head and neck. It presents as a variety of lesions, and so is considered a great mimicker, leading to a delay in diagnosis and evidencing the importance of biopsy with immunohistochemistry confirmation. There are few reports of extremity involvement in patients with pre-existing chronic lymphoedema, or exposure to radiation therapy. We report the case of an 82-year-old woman with lower limb extensive cutaneous involvement, distant metastatic disease, and poor therapy response. Its rare location without predisposing factors highlights the need to raise awareness about this disease. LEARNING POINTS: Extremity involvement of cutaneous angiosarcoma has been rarely described. The marked heterogeneity in presentation leads to a delay in diagnosis and poor prognosis, so the index of suspicion should be high. The cases reported in the literature describe a well-known relationship between cutaneous angiosarcoma and predisposing factors, but its absence should not exclude the diagnosis. This case highlights the importance of recognizing and biopsy suspected skin lesions for immunohistochemistry diagnostic confirmation.